2017
DOI: 10.1080/13548506.2017.1316412
|View full text |Cite
|
Sign up to set email alerts
|

‘A necessary evil’: associations with taking medication and their relationship with medication adherence

Abstract: Cognitive factors, like beliefs, have been studied extensively as determinants of medication adherence, while affect associated with taking medicines has been studied much less. In the present study (N = 525), we investigated affect by assessing patients' first associations with taking their medicines. Results showed that these associations were related to self-reported medication adherence: Patients who associated taking medicines with negative affect were the least adherent, while those associating taking me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In a study aimed at investigating the first associations, patients had with taking their medication and whether these associations were related to adherence behaviour, the highest mean adherence rates were found for participants reporting “necessity” followed by “routine”. Their study found that negative associations reported were mostly of an emotional nature, whereas positive associations were mostly of a cognitive nature (Kleppe et al., 2017 ). This confirms the necessity of involving the patient in their own care, for us to listen to their feelings regarding medication and for patients to process what the treatment entails.…”
Section: Discussionmentioning
confidence: 99%
“…In a study aimed at investigating the first associations, patients had with taking their medication and whether these associations were related to adherence behaviour, the highest mean adherence rates were found for participants reporting “necessity” followed by “routine”. Their study found that negative associations reported were mostly of an emotional nature, whereas positive associations were mostly of a cognitive nature (Kleppe et al., 2017 ). This confirms the necessity of involving the patient in their own care, for us to listen to their feelings regarding medication and for patients to process what the treatment entails.…”
Section: Discussionmentioning
confidence: 99%
“…This study was approved by the Internal Committee Biomedical Experiments of Philips Research. It was part of a larger investigation (see Kleppe et al, in press).…”
Section: Methodsmentioning
confidence: 99%
“…The barrier questionnaire was developed and validated in an earlier study (data not shown). First, a list of 25 adherence determinants was composed, based on existing evidence in the literature about their relationship with medication nonadherence [8,[23][24][25][26][27]. Second, an extensive questionnaire was composed by assessing this list of 25 determinants making use of existing (shorter versions of) instruments for the constructs for which they existed and self-composed items when instruments did not exist.…”
Section: Patient Questionnairementioning
confidence: 99%